KRISIS LINGKUNGAN HIDUP DALAM PERSPEKTIF AL-QUR’AN - Cholil Zuhdi, Achmad (Program Studi Perbandingan Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2012)
The environmental crisis is a picture of a spiritual crisis that had plagued most of humanity due to the human deification to absolutize humanism above nature. Consequently, there was exploitation of nature in the name of human rights priorities. It needs immediate rescue through the vision of traditional Islam, which has perspectives of effective environmental protection and basic. Without the introduction and implementation of traditional Islamic teachings, it would lead to the long environmental crisis. And this paper try to explore the anxiety and conceptualization of Koran to resolve the environmental crisis, based on the traditional Islamic values derived from the verses of the Koran